Waiting for a post-postmodern Narcissus. Postmodern iconoclastic irony as a double-edged sword - Chalupa, Jiri (Romanica Olomucensia, 2019)
The present text shows, in the first part, specific examples of how the ironic, sarcastic, parodic, and iconoclastic procedures often used by many authors of postmodern prose destroy/deconstruct what in this work are called ``auras'' and which can be designated with the synonym ``small myth'' about certain social phenomena, a ``minimyth'' that helps some social activities and processes to function smoothly. This iconoclastic behaviour, both of a deliberate type and the type that occurs as ``collateral damage'', will be observed in fragments of texts by three Spanish authors: Eduardo Mendoza, Arturo Perez-Reverte, and Juan Eslava Galan. In the second part, the paper will focus on the consequences, both actual and potential, of the process of deconstructing myths and ``auras'' that originally aroused hopes and illusions about a new open space for changes and transformations in the sense of a freer, more rational and more functional thought and society. Then, relying in part on the analyses of respected critical minds of the last four decades, such as, for example, Gilles Lipovetsky, David Harvey, or David Foster Wallace, a rather negative and in some aspects even alarming balance of the actual results of those historical transformations will be presented. And that in various fields of social life: in politics, in personal intercommunication, in the ways of seeking information, in the ways of spending free time, in the desire to find a stable substitute for the relativized and discredited Truths. Next, a brief analysis will be performed of the new phenomena that appear within postmodernity, such as individualistic narcissism and the consequent egotism, the dictatorship of fashion and of the simplistic image, the society of seduction, the slavery of the self, etc.
Keywords: irony; parody; iconoclasm; postmodernity; deconstruction; demystification